A comprehensive population‐based characterization of heart failure with mid‐range ejection fraction. (25th September 2017) - Koh, Angela S.; Tay, Wan Ting; Teng, Tiew Hwa Katherine; Vedin, Ola; Benson, Lina; Dahlstrom, Ulf; Savarese, Gianluigi; Lam, Carolyn S.P.; Lund, Lars H.
Abstract : Aims: Clinical features and outcomes in the novel phenotype heart failure with mid‐range ejection fraction [HFmrEF, ejection fraction (EF) 40–49%] were compared with heart failure with reduced EF (HFrEF, EF <40%) and preserved EF (HFpEF, EF ≥50%). Methods and results: In the Swedish Heart Failure Registry, we assessed the association between baseline characteristics and EF group using multivariable logistic regressions, and the association between EF group and all‐cause mortality using multivariable Cox regressions. Of 42 061 patients, 56% had HFrEF, 21% had HFmrEF, and 23% had HFpEF. Characteristics were continuous for age (72 ± 12 vs. 74 ± 12 vs. 77 ± 11 years), proportion of women (29% vs. 39% vs. 55%), and 13 other characteristics. Coronary artery disease (CAD) was distinctly more common in HFrEF (54%) and HFmrEF (53%) vs. HFpEF (42%); adjusted odds ratio for CAD in HFmrEF vs. HFpEF was 1.52 [95% confidence interval (CI) 1.41–1.63]. For six additional characteristics HFmrEF resembled HFrEF, for seven characteristics HFmrEF resembled HFpEF, and for 10 characteristics there was no pattern. The adjusted hazard ratio (HR) for mortality in HFrEF vs. HFpEF was 1.35 (95% CI 1.14–1.60) at 30 days, 1.26 (95% CI 1.17–1.35) at 1 year, and 1.20 (95% CI 1.14–1.26) at 3 years. In contrast, HFmrEF and HFpEF had a similar prognosis (HR 1.06, 95% CI 0.86–1.30 at 30 days; HR 1.08, 95% CI 1.00–1.18 at 1 year; and HR 1.06, 95% CI 1.00–1.12 at 3 years). Three‐year mortality was higher in HFmrEF than in HFpEF in the presence of CAD (HR 1.11, 95% CI 1.02–1.21), but not in the absence of CAD (HR 1.02, 95% CI 0.94–1.12; P for interaction <0.001). Conclusions: HFmrEF was an intermediate phenotype, except that CAD was more common in HFmrEF and HFrEF vs. HFpEF, crude all‐cause mortality was lower in HFmrEF and HFrEF, adjusted all‐cause mortality was lower in HFmrEF and HFpEF, and CAD portended a higher adjusted risk of death in HFmrEF and HFrEF.